The Analytics Mandate (MIT Sloan Management Review, 2014)
Based on a global executive survey with 2,000+ respondents and interviews with more than thirty executives, MIT Sloan Management Review and SAS Institute Inc. report that analytics has become a common path to business value. Organizations are now being challenged to step up their use of analytics, whether they are just getting started or are seasoned practitioners. The implications for industry competition are coming into focus—companies that incorporate analytics into their culture are finding success in the new digital era.